PENGUATAN LITERASI DIGITAL UNTUK REMAJA DI PONDOK BENOWO INDAH RT 03 RW 08 - Yeni Probowati; Dewanto Dewanto; Lambang Erwanto Suyadjid (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
The advancement of information technology has a major influence on social interaction patterns among teenagers while also impacting the spread of hoaxes and cyberbullying. This activity supports one of the leading areas of Community Service, namely Regional and Village Development. Partners in this activity are youth of Pondok Benowo Indah RT 03 RW 08. Low digital literacy among the youth of Pondok Benowo Indah RT 03 RW 08 triggers vulnerability to information that is not properly verified and can affect their mindset and social behavior. Teenagers have different reasons why they use their gadgets, some want to seek pleasure or entertainment, some want to fulfill their need for information and some simply fulfill their social desires by interacting on social media and of course not forgetting online games. These pleasurable activities are what trigger someone to become addicted to consuming the internet, especially social media and online games. The methods used in this activity are socialization, training and mentoring on digital literacy, hoax identification, the impact of the spread of false information and ethics in social media and playing online games. The purpose of this activity is to increase the understanding and awareness of teenagers in Pondok Benowo Indah RT 03 RW 08 in preventing hoaxes and cyberbullying when they surf the internet. At the end of this activity, it is hoped that teenagers have responsibility and critical thinking regarding the use of digital technology to support the formation of the golden generation of 2045.